Preparation and mechanical properties of LC cladding layer for friction parts - Jiang, Lingbo (Frontiers in Mechanical Engineering, 2024)
In the actual engineering operation, there are some components facing high frequency friction, which have high damage rate and poor direct replacement benefit. For these components, if effective remanufacturing can be carried out, the sustainable utilization of resources can be realized, which has high economic benefits and environmental protection significance. Therefore, based on the idea of remanufacturing, taking 42CrMo as the raw material of engine piston pin hole, laser cladding technology and ultrasonic rolling technology are used to prepare the cladding layers of Fe, Ni and Co three different substrates. Their properties are tested. The experimental results showed that the Co based cladding layer with ultrasonic rolling technology performed best. The surface roughness reduced by 1.02μm, only 0.14μm. The microhardness increased by 101.39%, with 795.38HV. The friction coefficient was 0.051. The friction rate at high temperature decreased by 85.71%, and it wasc 1.2%. The friction at high temperature was reduced by 79.24%, with 0.9%. Co based cladding layer combined with ultrasonic rolling technology shows the best performance, which can effectively realize the remanufacturing of engine piston pin hole, providing technical reference and data support for the remanufacturing process of high-frequency friction components.